THE INFLUENCE OF PRICE PERCEPTIONS AND SERVICE QUALITY ON CONSUMER SATISFACTION IN IMPLEMENTING STRATEGY AT PT PRIMAJASA CIREBON - Ridhasyabina, Muna; Faujani, Fajrina Putri; Nugraha, Rizky; Puspita, Rahista Maya; Erpina, Evi; Dewi, Puspita; Azmy, Dzikry Ulyl; Wibowo, Sandi Nasrudin (Universitas Muhammadiyah Tangerang, 2024)
This research aims to determine the influence of price perceptions and service quality on customer satisfaction at PT. PrimajasaPerdanaraya Utama Cirebon branch. This research uses quantitative methods. The population in this study were all consumers of PT PrimajasaPerdanaraya Utama in the Cirebon area with a total sample of 56 respondents. Data processing uses SPSS version 26 application software. The analytical methods used in this research are instrumental tests (validity tests and reliability tests), classical assumption tests (normality tests, multicollinearity tests and heteroscedasticity tests), hypothesis tests (t tests and t tests). f). The research results show that Price Perception (X1) has no partial effect on Consumer Satisfaction (Y) and Service Quality (X2) has a partial effect on Consumer Satisfaction (Y). These results are shown by t count > t table (2.006). Simultaneously Price Perception (X1) and Service Quality (X2) have a positive and significant effect on Consumer Satisfaction (Y) with a calculation of fcount>ftable 37.825>3.17.